Personalized Exercise for Adolescents With Diabetes or Obesity - Faulkner, Melissa Spezia (Biol Res Nurs, 2013)
OBJECTIVE: This study examined adherence to a personalized, community-based exercise intervention by sedentary adolescents with type 1 or type 2 diabetes or those with obesity. RESEARCH DESIGN AND METHODS: We conducted a pretest–posttest investigation to explore the application of an individualized exercise prescription based upon current fitness level for 39 adolescents (20 with type 1 diabetes, 9 with type 2 diabetes, and 10 obese) over 16 weeks in community settings. Subjects were recruited from a university-based pediatric endocrinology clinic in the southwestern United States. Adherence to the exercise prescription was monitored using accelerometers over the entire intervention period. RESULTS: Moderate-to-vigorous physical activity (MVPA) levels significantly increased over sedentary baseline values (p < .001), but the average of 42.5 ± 22.1 min/day of MVPA determined at the end of the study was still less than the recommended 60 min/day. Perceptions of health were significantly increased for the total group following the intervention (p = .008). For those with type 1 diabetes, there was a significant association between MVPA duration and percentage change in HbA(1c) (r = −.526, p = .02). CONCLUSIONS: Recruitment and retention of adolescent participation in daily exercise is challenging. Personalized approaches that include adolescent choices with family support and ongoing motivation can improve individual exercise adherence and a sense of personal health.